Price theory - Landsburg, Steven E. (South-Western,Cengage Learning, 2008)
The exciting new eighth edition of "Price Theory, International Edition" delivers a text that will both challenge and intrigue students as it equips them with the tools and skills to apply economic principles to the world around them. Inductive, hands on, and highly interactive, the book is intellectually rigorous yet student-friendly, with countless applications and resources to help readers fully understand concepts. Using the same humorous, easy-to-read approach as his popular "The Armchair Economist", Steven Landsburg offers thorough coverage of traditional topics of intermediate price theory as well as emerging issues, such as the economics of information. Social welfare is a unifying concept throughout